2015
DOI: 10.7150/thno.13033
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Molecular Delivery with Sequential Low-Energy Sonoporation Bursts

Abstract: Microbubbles interact with ultrasound to induce transient microscopic pores in the cellular plasma membrane in a highly localized thermo-mechanical process called sonoporation. Theranostic applications of in vitro sonoporation include molecular delivery (e.g., transfection, drug loading and cell labeling), as well as molecular extraction for measuring intracellular biomarkers, such as proteins and mRNA. Prior research focusing mainly on the effects of acoustic forcing with polydisperse microbubbles has identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…The peak sonoporation efficiency we achieved (36%) is similar to what has previously been reported for microbubble sonoporation (28–39% efficiency) [6, 30, 31], albeit with lower cell viability (70% viability for PCCA sonoporation vs. 90–96% viability for MB sonoporation [6, 30, 31]). However, these microbubble sonoporation studies employ unique strategies to increase sonoporation efficiency and minimize cell death, making it difficult to make direct comparisons.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The peak sonoporation efficiency we achieved (36%) is similar to what has previously been reported for microbubble sonoporation (28–39% efficiency) [6, 30, 31], albeit with lower cell viability (70% viability for PCCA sonoporation vs. 90–96% viability for MB sonoporation [6, 30, 31]). However, these microbubble sonoporation studies employ unique strategies to increase sonoporation efficiency and minimize cell death, making it difficult to make direct comparisons.…”
Section: Discussionsupporting
confidence: 86%
“…For example, McLaughlan et al achieved their highest viable sonoporation using a combination of (1) targeted microbubbles that increase cell-microbubble interactions and (2) chirp frequency excitation to maximize the response of their polydisperse microbubbles [6]. Song et al found that using monodisperse 2.0-μm microbubbles resulted in the highest sonoporation and viability after a single ultrasound treatment [31]. We believe that with further optimization of our PCCA-mediated sonoporation methods, we will be able to match the sonoporation efficiencies and viabilities achieved with microbubbles.…”
Section: Discussionmentioning
confidence: 99%
“…Larger shear stress have been shown to correlate with higher propidium iodide uptake, which shows that the pores either stay open longer or are larger. 27 Likewise, larger holes 129 , higher sonoporation efficiency 40 and spatiotemporal control over pore formation 106 can be achieved by using two successive sonoporation pulses with a different pressure.…”
Section: Acoustic Settings Influencing Microbubble-cell Interactions mentioning
confidence: 99%
“…During biofilm formation, surface-adherent extracellular matrices of the biofilm act as a barrier to antibiotic diffusion, which limits the exposure of intracellular bacteria in the biofilms to superficial antibiotics. Ultrasound (US) has been widely acknowledged as a promising approach to overcome these obstacles by enabling increased permeability for gene/drug delivery (13,14). Ultrasound exposure induces sonoporation, which may transiently disrupt the cell membrane and increase the permeability of the membrane to promote transportation of membrane-impermeable agents, such as nanoparticles or antibodies, into cells or tissues in preclinical studies.…”
mentioning
confidence: 99%